Pupillometry to differentiate idiopathic hypersomnia from narcolepsy type 1 - Rach, Héloïse; Reynaud, Eve; Kilic‐Huck, Ulker; Ruppert, Elisabeth; Comtet, Henri; Roy de Belleplaine, Virginie; Fuchs, Fanny; Van Someren, Eus J. W.; Geoffroy, Pierre A.; Bourgin, Patrice (Journal of sleep research, 2023)
Idiopathic hypersomnia is poorly diagnosed in the absence of biomarkers to distinguish it from other central hypersomnia subtypes. Given that light plays a main role in the regulation of sleep and wake, we explored the retinal melanopsin‐based pupil response in patients with idiopathic hypersomnia and narcolepsy type 1, and healthy subjects. Twenty‐seven patients with narcolepsy type 1 (women 59%, 36 ± 11.5 years old), 36 patients with idiopathic hypersomnia (women 83%, 27.2 ± 7.2 years old) with long total sleep time (> 11/24 hr), and 43 controls (women 58%, 30.6 ± 9.3 years old) were included in this study. All underwent a pupillometry protocol to assess pupil diameter, and the relative post‐illumination pupil response to assess melanopsin‐driven pupil responses in the light non‐visual input pathway. Differences between groups were assessed using logistic regressions adjusted on age and sex. We found that patients with narcolepsy type 1 had a smaller baseline pupil diameter as compared with idiopathic hypersomnia and controls ( p < 0.05). In addition, both narcolepsy type 1 and idiopathic hypersomnia groups had a smaller relative post‐illumination pupil response (respectively, 31.6 ± 13.9% and 33.2 ± 9.9%) as compared with controls (38.7 ± 9.7%), suggesting a reduced melanopsin‐mediated pupil response in both types of central hypersomnia ( p < 0.01). Both narcolepsy type 1 and idiopathic hypersomnia showed a smaller melanopsin‐mediated pupil response, and narcolepsy type 1, unlike idiopathic hypersomnia, also displayed a smaller basal pupil diameter. Importantly, we found that the basal pupil size permitted to well discriminate idiopathic hypersomnia from narcolepsy type 1 with a specificity = 66.67% and a sensitivity = 72.22%. Pupillometry may aid to multi‐feature differentiation of central hypersomnia subtypes.